The Sarkozy Presidency Breaking the Mould? - Raymond, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Sarkozy came to power promising radical political and social change while simultaneously developing a presidential persona that melded the public and the personal under the glare of media attention, unparalleled in the French Fifth Republic. This volume provides a detailed analysis of the fit between his ambitions and the outcomes of his presidency.
Keywords: Europe—Politics and government; Elections; Political science; Public policy; Political theory; Political communication; European Politics; Electoral Politics; Political Science; Public Policy; Political Theory; Political Communication